Blood Pressure Control and Adherence to Drug Treatment in Patients with Hypertension Treated at a Specialized Outpatient Clinic: A Cross-Sectional Study - Guimarães MCLP; Coelho JC; Silva GV; Drager LF; Gengo e Silva Butcher RDC; Butcher HK; Pierin AMG (Patient Preference and Adherence, 2021)
Mayra Cristina da Luz Pádua Guimarães,1 Juliana Chaves Coelho,1 Giovanio Vieira da Silva,2 Luciano Ferreira Drager,2,3 Rita de Cassia Gengo e Silva Butcher,1 Howard K Butcher,4 Angela Maria Geraldo Pierin1 1Graduate Program in Adult Health Nursing (PROESA), University of São Paulo Nursing School, São Paulo, SP, Brazil; 2Hypertension Unit, Renal Division, University of São Paulo Medical School, São Paulo, SP, Brazil; 3Hypertension Unit, Heart Institute (InCor), University of Sao Paulo Medical School, São Paulo, SP, Brazil; 4Christine E. Lynn College of Nursing, Florida Atlantic University, Boca Raton, FL, USACorrespondence: Mayra Cristina da Luz Pádua GuimarãesGraduate Program in Adult Health Nursing (PROESA), University of São Paulo Nursing School, São Paulo, SP, BrazilEmail mayraguimaraes@usp.brObjective: To evaluate and identify variables associated with the control of hypertension and adherence to antihypertensive drug treatment in a group of patients with hypertension monitored in a specialized, highly complex outpatient service.Methods: A prospective, cross-sectional study was carried out in the hypertension unit of a tertiary teaching hospital. Patients diagnosed with hypertensive aged 18 years and over and accompanied for at least six months were included in the study. Patients with secondary hypertension and pregnant women were excluded. The sample consisted of 253 patients. Adherence/concordance to antihypertensive treatment was assessed using the Morisky Green Levine Scale. Blood pressure control was set for values less than 140/90 mmHg. Variables with p≤ 0.20 in univariate analysis were included in multiple logistic regression. The level of significance adopted was p ≤ 0.05.Results: Most of patients were white, married and women, with a mean age of 65 (13.3) years old, low income, and education levels. Blood pressure control and adherence were observed in 69.2% and 90.1% of the patients, respectively. Variables that were independently associated with blood pressure control were (OR, odds ratio; CI, 95% confidence interval): married marital status (OR 2.3; CI 1.34– 4.28), use of calcium channel blockers (OR 0.4; CI 0.19– 0.92) and number of prescribed antihypertensive drugs (OR 0.78; CI 0.66– 0.92). Adherence was not associated with any of the variables studied.Conclusion: There was a high frequency of patients with satisfactory adherence to antihypertensive drug treatment. Blood pressure control was less frequent and was associated with social and treatment-related factors.Keywords: hypertension, control, adherence, pharmacological treatment